Determinants of saving behavior among self-employed individual / Mohd Huzeer Mohamad Zaid and Fatin Nabila Abdul Rashid - Mohamad Zaid, Mohd Huzeer; Abdul Rashid, Fatin Nabila (Faculty of Business and Management, 2014)
Savings play an important role in economic development. Growth theories have shown that savings is a necessary ingredient to finance investment which will enhance a country’s productivity. The purpose of this study is to investigate the determinants of saving behavior among self-employed individuals. The factors are deriving from saving behavior, financial stress and financial management. The study follows descriptive research using survey methods. A set of questionnaires with four (4) point likert scale was developed and 100 questionnaires were distributed to all self-employed individuals. Frequency distribution, reliability test, correlation analysis and regression analysis has been chosen as the method to find the result. The findings indicate that a financial management is the most determinants that influence the saving behavior than financial stress.